Post-pandemic advertising and tourism studies in Africa - Mkwizu, Kezia H. (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2024)
Tourism studies in Africa are increasing in order to provide information and guide the sector. On 5 May 2023, the World Health Organization (WHO) declared COVID-19 as no longer a pandemic. Therefore, it is crucial for more research after the pandemic to reflect the effects of the pandemic in the post period particularly advertising as more nations need to attract as many tourists as possible to visit their destinations. This paper is motivated to explore tourism studies in Africa. The main objective is to explore post-pandemic advertising and tourism studies in Africa. The methodology deployed for this paper is the systematic literature review method. To address the main objective, this study poses the question “What are the post-pandemic types of advertising and topics of tourism studies in Africa?” The findings indicate that there are few studies in the post-pandemic addressing advertising and topics of tourism studies. The few existing studies have shown that social media advertising, internet advertising and exhibition are being used in the post-pandemic and topics such as promotion strategies and travel information have been covered but areas of artificial intelligence needs research to further understand its impact on advertising in the tourism industry within Africa.